2012
DOI: 10.1002/anie.201201708
|View full text |Cite
|
Sign up to set email alerts
|

(IscS‐IscU)2 Complex Structures Provide Insights into Fe2S2 Biogenesis and Transfer

Abstract: The center of attention: IscS cysteine desulfurases and IscU scaffolds are involved in biological iron–sulfur cluster assembly. The X‐ray structure of an anaerobically produced, mutated (Fe2S2‐(IscS‐IscUD35A))2 complex reveals a cluster coordinated by three IscU cysteines and the IscS active cysteine (see picture). In air‐exposed crystals the cluster is oxidized to an Fe2S–S center; D35 is essential for complex dissociation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
170
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 31 publications
6
170
0
1
Order By: Relevance
“…Consistent with this hypothesis are studies by Marinoni et al (42), who solved the crystal structure of the IscS-IscU complex from Archaeoglobus fulgidus. In the crystal structure the participation of the catalytic IscS-Cys321 as a transient ligand in the formation of the 2Fe2S cluster on IscU was resolved (42). Thus, during FeS cluster formation, a portion of IscS would not be available for acceptor proteins like TusA or ThiI.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis are studies by Marinoni et al (42), who solved the crystal structure of the IscS-IscU complex from Archaeoglobus fulgidus. In the crystal structure the participation of the catalytic IscS-Cys321 as a transient ligand in the formation of the 2Fe2S cluster on IscU was resolved (42). Thus, during FeS cluster formation, a portion of IscS would not be available for acceptor proteins like TusA or ThiI.…”
Section: Discussionmentioning
confidence: 99%
“…This result favors in turn a concerted mechanism for Fe-S cluster assembly by ISC, where two ferrous ions bind simultaneously the first persulfide S 0 from the active Cys residue of IscS at the assembly site of IscU and reduce it to S 2− . We have already suggested such mechanism based on the Archeoglobus fulgidus (IscS-IscU) 2 complex structure (27).…”
Section: Discussionmentioning
confidence: 99%
“…Two Isu1 subunits, one from each [Yfh1] 3 ⅐[Isu1] 3 sub-complex, face each other with their respective [2Fe-2S] coordinating sites formed by the invariant Cys-69, Cys-96, Cys-139, and His-138 residues, known to be involved in Fe-S cluster coordination (Fig. 9A) (15,33,34). In each site, these residues are within ϳ2-4 Å from each other, in a manner that appears suitable to coordinate one [2Fe-2S] cluster (Fig.…”
Section: Cross-linked Partners Total Cross-linked Peptidesmentioning
confidence: 99%
“…The crystal structure of an Escherichia coli [IscS]⅐[IscU] complex (PDB 3 code 3LVL) showed an elongated heterodimer consisting of one IscS and one IscU subunit (14), and furthermore the crystal structure of an Archaeoglobus fulgidus [IscS] 2 ⅐[IscU] 2 complex (PDB code 4EB5) showed an elongated heterotetramer consisting of two IscS and two IscU subunits (15). Additional studies demonstrated similar bacterial and yeast heterotetramers in which a dimer of IscS/ Nfs1 binds to one IscU/Isu1 monomer at each end, and it was further proposed that one CyaY/Yfh1 monomer could bind in a pocket between the cysteine desulfurase and the scaffold (10, 16 -18).…”
mentioning
confidence: 99%